2022
DOI: 10.1002/admt.202200209
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and Breathable Ion Gel‐Based Sensors toward Multimodal Sensing Ability

Abstract: Polymer thin‐film sensors have attracted considerable attention in various applications owing to their highly transparent, flexible, and gas‐permeable features. However, conventional thin‐film sensors based on nanomaterials suffer from poor selectivity in sensing targets and scalability of functions. Therefore, a new approach is required for achieving higher selectivity with simple processibility. This study proposes highly transparent, ultra‐flexible, and gas‐permeable polymer thin‐film sensors using ion gels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Previous studies have confirmed that the conductivity of ILs was positively correlated with temperature because of the movement of ions driven by the temperature. , There was a large amount of ILs in the resulting gel, so the resistance of the gel presented an opposite trend to the temperature change. Based on this law, the gel could be constructed as the temperature sensor, and the temperature change can be converted into digital electrical signals (Figure a).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have confirmed that the conductivity of ILs was positively correlated with temperature because of the movement of ions driven by the temperature. , There was a large amount of ILs in the resulting gel, so the resistance of the gel presented an opposite trend to the temperature change. Based on this law, the gel could be constructed as the temperature sensor, and the temperature change can be converted into digital electrical signals (Figure a).…”
Section: Resultsmentioning
confidence: 80%
“…The ionic liquids (ILs) are organic salts, which are composed of anions and cations. Their melting point is generally less than 100 °C, and they remain in the liquid state at room temperature. Because of the specific composition, the ILs hold outstanding advantages of low saturated vapor pressure and high ionic conductivity. Therefore, the introduction of ILs into the hydrogel can not only endow the hydrogel with the anti-resistance to volatile but also improve the ionic conductivity of the resulting hydrogel. Besides, because the movement of ions is positively correlated with temperature, the resistance of gels containing ILs shows a change law contrary to temperature, indicating the gel can be applied in the temperature-sensing devices. , As the ILs have neither stretchability nor elasticity, the compressibility and extensibility of the hydrogels modified by ILs are relatively poor.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of active materials is a key factor to achieve the versatility of flexible sensors. To date, many materials have been employed to fabricate multifunctional flexible sensors, including carbon-based materials, 8,9,13,14 ionic liquids, 3,7,15,16 conductive polymers, 10 and metallic nanomaterials. 17 chemical window, high chemical and thermal stability, etc., which is an ideal multifunctional sensing material candidate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24−26 Using this mechanism, an ultrasensitive interfacial supercapacitive sensing pressure sensor can be fabricated. Moreover, the electrical properties of i-skin also change depending on humidity, 15 and previous studies have developed ionic sensors that respond to humidity. 27−29 These two stimuli have not only different sensing mechanisms but also different output electrical signals.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation